Ultimate bug rumble - Pallotta, Jerry (Pallotta, Jerry. Who would win., 2017)
"This nonfiction reader compares and contrasts 16 ferocious insects. Readers will learn about each animal's anatomy, behavior, and more. Then compare and contrast the battling animals before finally discovering the winner!" -- Amazon.com.